Towards a science of touch, part I - Hsu, E (Carfax Publishing, 2000)
This paper is about a pre-modern 'science of touch' - Chinese pulse diagnostics - which was the aspect of Chinese medicine most admired by physicians in early modern Europe. The paper first provides some historical information on Chinese pulse diagnostics in Europe and then details how it was presented to an 18th-century readership. At last, it points out that Chinese physicians had developed an elaborate system for distinguishing between various experiences of touch. From an outsider's viewpoint, one could say that they already had an idea of calibration and made measurements in respect of a calibrated condition. Since they put their fingertips on the wrist of their patients and actively palpated it, one can say that their 'science of touch' was developed in respect of 'active touch'. This in contrast to the 'science of touch' developed by psychophysicists of the modern West, who have been interested primarily in 'passive touch'.